Analisis Kontribusi Pajak Hotel dan Pajak Restoran Terhadap Pendapataan Asli Daerah: Studi Pada Kota Wisata Bukittinggi - Rahayu Nengsih; Boni Saputra (Asosiasi Ilmuwan Administrasi Negara (AsIAN), 2025)
This study aims to analyze the contribution of hotel tax and restaurant tax to the local revenue of Bukittinggi City for the period 2019-2024, identify factors that influence fluctuations in hotel tax revenue and declines in restaurant tax revenue, and examine strategies for optimizing the management of these two taxes. This study uses a mixed method approach with a descriptive research design. Quantitative data were analyzed using contribution ratios, while qualitative data were obtained through in-depth interviews with officials from the Bukittinggi City Finance Agency and analyzed descriptively. The results show that the average contribution of hotel tax to PAD is 13.32% (category “Less”) and restaurant tax is 6.46% (category “Very Less”). The influencing factors include: (1) external factors such as the COVID-19 pandemic, fluctuations in the number of tourists, macroeconomic conditions, natural disasters, and regulatory changes (2) internal factors such as low compliance among small taxpayers, weak administrative systems, limited human resources, and suboptimal supervision. The optimization strategies implemented include intensification through data updates and increased supervision, extensification through active data collection, digitization of the taxation system, increased compliance through socialization and law enforcement, inter-agency coordination, and strengthening of human resource capacity and services.